Memahami Perilaku Penerimaan Mobile Payment di Kalangan Muda (Mahasiswa) Menggunakan Pengembangan Model IMMPA - Dewi Widyawati; Wing Wahyu Winarno (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Since the emerge of digital commerce in the form of m-commerce, mobile payment services have started to get global attention. Easy access to mobile payment services, the benefits offered, and the clarity of the regulations that govern them, have not yet fully attracted the interest of all Indonesian people to use them. Changing the behavior of transactions to mobile payments in line with access to the digital economy, which has the potential to increase a country's economic growth even to the macro level. This study will identify the determinants of actual acceptance and use of mobile payment services among young people. Younger users are more likely to receive and adopt technology and technology services, especially young people who are in the campus environment, so students will be taken as respondents in this study. This study uses the Integrated Model on Mobile Payment Acceptance (IMMPA) by Di Pietro et al. (2015) and adding one construct that is relevant to the factors that influence the use of mobile payment services, namely Trust. Another new construct developed from the IMMPA model is Perceived Security which is linked to Trust. The theoretical framework was tested using the Structural Equation Model (SEM). The research findings show that Intention to Use strongly influences User's Behavior, while Intention to Use is strongly influenced by Trust. Perceived security influences Trust. Ease of Use affects Usefulness